Çarlık Rusya’nın Kafkas Hattı’nı İnşası ve Kuzey Kafkasya’da hâkimiyet kurma mücadelesi - ÇAYCIOĞLU, SERDAR OĞUZHAN (My University, 2022)
The Caucasus Line has an important function in the spread of Tsarist Russia in the Caucasus and to establish a long-term rule. In this study, the structure, features and advantages of the line, which is connected with the fortified settlements (stanitsa), for the Russian domination in the region are examined. The Russian settlement of Cossacks on the banks of the Kuban and the Terek rivers and the castles built on the line are very important for the administrative-military order in the region. These activities of the Russians aimed at breaking the contact between the Ottoman Empire and the North Caucasus through the Crimean Khanate. The construction of these fortresses by the Russians in Terek in the 16th century turned into a diplomatic crisis between the Ottoman Empire and Russia. The construction of the Georgian Military Road from Vladikavkaz to Tbilisi also played an important role in the Russian landing in the South Caucasus. This road is also the main route where Tsarist Russia conducted military operations against mountain peoples it wanted to subordinate to ensure its dominance in the mountainous regions. Russia has also organized numerous expeditions to the mountainous regions of the Caucasus for the safety of this road, where communications and military dispatches are carried out. This article examines the campaigns of General Velyaminov, who commanded the Caucasus Line for many years, and Baron Rozen, the Commander-in Chief of the Russian Armies in the Caucasus, between 1831-1832.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC)